Quercetin Affects Spermatogenesis-Related Genes of Mouse Exposed to High-Cholesterol Diet - Changwon Yang; Hyocheol Bae; Gwonhwa Song; Whasun Lim (The Korean Society of Animal Reproduction and Biotechnology, 2020)
A high-cholesterol diet can reduce male fertility. However, it is not known whether a high-cholesterol diet can regulate the expression of genes involved in sperm maturation and sperm fertilizing ability. Quercetin, a natural product, is known to have cytoprotective effects by regulating lipid metabolism in various cell types. This study aimed to confirm the expression of genes involved in sperm maturation in the testes of mice fed a high-cholesterol diet and to determine whether quercetin can reverse the genetic regulation of cholesterol. Mice were divided into groups fed a normal chow diet and a high-cholesterol diet. Mice fed the high-cholesterol diet were dose-dependently supplemented with quercetin for 6 weeks. Investigations using quantitative PCR and in situ hybridization revealed that the high-cholesterol diet alters the expression of genes associated with sperm maturation in the testes of mice, and this was reversed with the supplementation of quercetin. In addition, the high-cholesterol diet regulated the expression of genes related to lipid metabolism in the liver of mice. Under a highcholesterol diet, quercetin can improve male fertility by regulating the expression of genes involved in sperm maturation.